2016
DOI: 10.1007/s11010-016-2737-7
|View full text |Cite
|
Sign up to set email alerts
|

Fads1 and 2 are promoted to meet instant need for long-chain polyunsaturated fatty acids in goose fatty liver

Abstract: Global prevalence of non-alcoholic fatty liver disease (NAFLD) constitutes a threat to human health. Goose is a unique model of NAFLD for discovering therapeutic targets as its liver can develop severe steatosis without overt injury. Fatty acid desaturase (Fads) is a potential therapeutic target as Fads expression and mutations are associated with liver fat. Here, we hypothesized that Fads was promoted to provide a protection for goose fatty liver. To test this, goose Fads1 and Fads2 were sequenced. Fads1/2/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
(85 reference statements)
2
21
0
Order By: Relevance
“…However, several conditions can significantly diminish the capacity of the liver for LCPUFA synthesis from their precursors thus affecting the hepatic levels of n-6 n-3 LCPUFAs, including (i) the lack of nutrients such as zinc [35]; (ii) the excessive ethanol consumption [36]; and (iii) the existence of certain polymorphisms in the gene sequences of Δ-5 and Δ-6 desaturases that reduces the activity of these enzymes [37]. An interesting situation related to the activity of Δ-5 and Δ-6 desaturases is liver steatosis, a pathological condition in which the oxidative stress of nutritional origin generated by fat overload (lipotoxicity) also results in a reduction in the desaturation capacity of the tissue with low levels of n-6 and n-3 LCPUFAs [14, 38, 39], effects that are also observed after a HFD [15, 40]. Also, in overfeeding conditions the increment in gene expression of Δ-5 and Δ-6 desaturase enzymes is not sufficient to compensate the reduction of n-6 and n-3 LCPUFAs [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several conditions can significantly diminish the capacity of the liver for LCPUFA synthesis from their precursors thus affecting the hepatic levels of n-6 n-3 LCPUFAs, including (i) the lack of nutrients such as zinc [35]; (ii) the excessive ethanol consumption [36]; and (iii) the existence of certain polymorphisms in the gene sequences of Δ-5 and Δ-6 desaturases that reduces the activity of these enzymes [37]. An interesting situation related to the activity of Δ-5 and Δ-6 desaturases is liver steatosis, a pathological condition in which the oxidative stress of nutritional origin generated by fat overload (lipotoxicity) also results in a reduction in the desaturation capacity of the tissue with low levels of n-6 and n-3 LCPUFAs [14, 38, 39], effects that are also observed after a HFD [15, 40]. Also, in overfeeding conditions the increment in gene expression of Δ-5 and Δ-6 desaturase enzymes is not sufficient to compensate the reduction of n-6 and n-3 LCPUFAs [39].…”
Section: Discussionmentioning
confidence: 99%
“…The substantial diminution in the hepatic levels of LCPUFAs by HFD, particularly those from the n-3 series (EPA, DHA and DPA), may be ascribed to the drastic reduction of the liver activity of desaturase enzymes achieved, considering their relevance in LCPUFA metabolism [15, 40]. This effect can be contributed by the diminution in the hepatic levels of the n-3 LCPUFA precursor ALA observed (Table 2) and by the enhancement in the oxidative stress status of the liver (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic Palmipedes are particularly susceptible to hepatic steatosis, and unlike human NAFLD, the fatty liver is nonpathological and reversible 16 . Goose liver has been widely studied by researchers as a good model to investigate the mechanism of lipid metabolism 17 . Since the miRNAs involved in fatty liver production in geese remain to be elucidated, an analysis of the functional miRNAs involved in goose hepatic steatosis was performed on.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Iwai et al [10] found that SCD1 affected apoptosis in mouse proximal tubular cells by regulating the MUFAs/SFAs ratio. Moreover, it was found that in overfeeding-induced goose fatty liver, the MUFAs/SFAs ratio significantly increased while the content of both palmitic acid and stearic acids decreased [4,11]. Thus, it can be generalized that SCD1 exerts an important role in regulating MUFAs/SFAs ratio.…”
Section: Introductionmentioning
confidence: 96%
“…In poultry production, this capacity is exploited for producing the fatty liver that is 5-to 10-fold larger than normal liver after 2-3 weeks of overfeeding [2,3]. Interestingly, its liver can develop serious steatosis without overt injury [4], showing minimal inflammation and other immune-related responses, which suggests that goose has different physiological and metabolic characteristics from mammals. In a previous study, the mRNA levels of tumor necrosis factor alpha (TNFα) was significantly downregulated by overfeeding in the goose liver [5].…”
Section: Introductionmentioning
confidence: 99%